Digital Marketing Strategy and Purchase Decisions on TikTok Shop: E-Trust as a Mediator - Reni Fitriningrum Reni; Mulyana (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2025)
This study aims to examine and analyze the influence of live streaming selling, affiliate marketing, and social media influencers on purchasing decisions on the TikTok Shop e- commerce platform in Semarang City, with E-Trust as a mediating variable. This phenomenon is driven by the increasing trend of e- commerce transactions in Indonesia and the significant development of online sales features, which triggers a shift in consumer behavior. The approach used is quantitative with an explanatory research method, where data was collected through questionnaires from 385 respondents who are TikTok Shop users in Semarang. The data analysis technique involves Outer Model and Inner Model tests using SmartPLS 4.0 to evaluate the mediating role of E-Trust. The results of the hypothesis analysis prove that live streaming selling, affiliate marketing, and social media influencers are all proven to have a positive and significant effect on E-Trust. Furthermore, E-Trust is also proven to have a positive and significant effect on Purchasing Decisions. specifically, E-Trust is proven to be able to mediate the relationship between live streaming selling and social media influencers on Purchasing Decisions. These findings are expected to provide theoretical contributions to the development of digital marketing science and offer practical implications for business actors in designing more effective promotional strategies on e- commerce platforms.